Experimental study on the influence of dielectric barrier discharge plasma on the atomization characteristics of aviation kerosene. (1st May 2022) - Yang, Kun; Chen, Lei; Liu, Guiming; Yang, Cong; Wang, Baohuai; Song, Peng; Wang, Jianming; Zeng, Wen
Highlights: DBD is used to explore a new way to optimize fuel atomization. He-assisting DBD can reduce droplets size and increase spray angle. Active-particle types in the atomization field are obtained. Abstract: In order to study the influence law of active particles on atomization characteristics of aviation kerosene and explore the key technologies of plasma application in fuel atomization auxiliary, the dielectric barrier discharge plasma nozzle was independently designed, and the experiments of He plasma jet spectrum diagnosis and fuel atomization characteristic were carried out. The active particle composition of He plasma jet was explored, and the influence of He volume flow rate and peak voltage on electron excitation temperature, SMD and spray cone angle were studied. The results show that He plasma ionizes the air in the surrounding space to produce active particles such as OH, O and He Ⅰ atoms. The electron excitation temperature varies between 3100 and 7300 K and reaches the maximum when the peak voltage is 11 kV. The influence of electric field application and He volume flow changes on the atomization characteristics are very obvious, specifically, as the peak voltage increases, the SMD decreases and the spray cone angle increases. Under the high peak voltage (12–13 kV), the increasing trend of the spray cone angle gradually slows down and stabilizes. As the volume flow of He increases, the SMD decreases and the spray cone angle increases. The difference in oil supply pressure will affect the atomization effect of plasma excited fuel. The specific realization is that under △Pinj = 0.05 MPa, the increase of He volume flow has little effect on the atomization effect. When △Pinj = 0.15–0.35 MPa, the change of peak voltage has a greater impact on SMD, while at a lower △Pinj (0.05–0.25 MPa), the change of peak voltage has a greater impact on the growth trend of the spray cone angle.